Anti malignant (HepG2, MOLT-3) Activity of One, Two, Three- Triazoles New Prepared Bearing Hetero Compounds in Baghdad (Indian Journal of Forensic Medicine & Toxicology, 2020)
In the current work, chemistry a group of related chemicals that are similar in structure or properties of new heterocyclic compounds were prepared from paraP.nitrobenzoic, acid. This work includes four parts: the first part Preparation of 5-(4-nitro phenyl)-1,33,4-thiaadiazol-2-amine by the reaction of p.pnitrobenzoic acid with thioseemicarbazide,the second part prepared 2-chloro-N-(5-(4-Nnitrophenyl)-1,3,4-thiadiazol2-yl) Aacetamide by reaction Chloroacetyl chloride with compound and part three contain reaction compound(2) with urea/thiourea to get compounds cyclization by using urea (thiourea) finally step reaction these compounds with different aldehydes and ketones in glacial acetic acid (6-10) , as shown in Scheme 1 The aim of present work is synthesis new derivatives of 1,2,3-Triazole having heterocyclic compounds on ring from the reaction of azine with a different reagent to give (1,2,3- Triazole) rings.The1,2,3-Triaazoles It has been derivatives A long time ago and has been Scout mainly for their potenitial in anti-tTumor chemotherapy the prepared of 11,2,3-Triazole financial products have good AAnti malignant (HepG2, MOLT-3) Activity. Many groupss have ccarried out focused research in this particularr